The Effect of Implementation Merdeka Curriculum and Learning Motivation on Students’ Learning Outcomes - Mita, Mita; Arafat, Yasir; Fitriani, Yessi (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines (1) the impact of the Merdeka Curriculum implementation, (2) the role of student learning motivation, and (3) their combined effects on learning outcomes in SMA/SMK schools across South Pemulutan District. Using a quantitative descriptive approach, data were collected from 127 students at SMA Negeri 1 and SMK Negeri 1 Pemulutan Selatan through questionnaires and documentation. Validity and reliability were ensured via construct validity and Cronbach’s Alpha, while normality, multicollinearity, and heteroscedasticity tests verified data suitability for analysis. The analysis revealed that: Merdeka Curriculum implementation positively influenced learning outcomes by 31.9%. Student motivation contributed 19.2% to improved academic performance. Together, these factors accounted for 36.3% of learning outcome variance, demonstrating significant synergistic effects. This study provides empirical evidence of Merdeka Curriculum’s efficacy in a localized context (South Pemulutan), while highlighting motivation’s complementary role a less explored dimension in curriculum evaluation studies. This study reinforces the need to align curriculum delivery with motivational strategies (e.g., student-centered activities). Supports the expansion of Merdeka Curriculum, emphasizing structured teacher training to maximize its impact. The findings bridge a critical gap by quantifying the dual influence of curriculum reform and motivation in Indonesian vocational and secondary education, offering a replicable framework for similar regional assessments.